2003
DOI: 10.1177/002215540305101011
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Variations Within Aneuploid Cancer Lines

Abstract: S U M M A R Y Aneuploid cancers exhibit a wide spectrum of clinical aggressiveness, possibly because of varying chromosome compositions. To test this, karyotypes from the diploid CCD-34Lu fibroblast and the aneuploid A549 and SUIT-2 cancer lines underwent fluorescence in situ hybridization (FISH) and DAPI counterstaining. The number of DAPI-stained and FISH-identified chromosomes, 1-22, X,Y, as well as structural abnormalities, were counted and compared using the 2 , Mann-Whitney rank sum test and the Levene's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 72 publications
(111 reference statements)
1
16
0
Order By: Relevance
“…1 ) for each cell line are listed in Table 2 . An excellent correspondence was found between these results and three of four previous studies of these cell lines (Diserens et al, 1981;Melcher et al, 2002;Isaka et al, 2003;Cottier et al, 2004): The modal chromosome number of the A549 cell line in this and previous studies was 63 ( Table 2 , Isaka et al, 2003;Cottier et al, 2004). Five of the A549 marker chromosomes in this study ( Table 2 ) were previously identified (Cottier et al, 2004): M1 = der(3)t(3;20), M2 = der(6)t(6;1), M4 = der(19)t(15;19), M5 = +der(19)t(15;19), and M6 = del(2).…”
Section: Comparison With Earlier Results Of Chromosome Classificationsupporting
confidence: 84%
See 1 more Smart Citation
“…1 ) for each cell line are listed in Table 2 . An excellent correspondence was found between these results and three of four previous studies of these cell lines (Diserens et al, 1981;Melcher et al, 2002;Isaka et al, 2003;Cottier et al, 2004): The modal chromosome number of the A549 cell line in this and previous studies was 63 ( Table 2 , Isaka et al, 2003;Cottier et al, 2004). Five of the A549 marker chromosomes in this study ( Table 2 ) were previously identified (Cottier et al, 2004): M1 = der(3)t(3;20), M2 = der(6)t(6;1), M4 = der(19)t(15;19), M5 = +der(19)t(15;19), and M6 = del(2).…”
Section: Comparison With Earlier Results Of Chromosome Classificationsupporting
confidence: 84%
“…The SUIT-2 cell line (derived from pancreatic adenocarcinoma, male) was propagated as previously described (Isaka et al, 2003). Specifically, cells were grown as a monolayer in appropriate media: DMEM (A549 and LN-18), Ham's F12K (LoVo) and McCoy's (SUIT-2) supplemented with L-glutamine, 10% FBS (Invitrogen Corporation, Carlsbad, CA), and sodium bicarbonate (Amersham Life Sciences; Arlington Heights, IL) (Nestor et al, 2001).…”
Section: Cell Culturementioning
confidence: 99%
“…These adenocarcinoma-derived cells contain wild-type p53 and pRb but do not express p16, a protein usually required for senescence [34]. The cell line is also aneuploid and contains chromosomal abnormalities [35], and heterogenous subpopulations [36]. We report that the DNA damage response to BrdU in these cells involves the activation of Chk1, Chk2 and p53.…”
Section: Introductionmentioning
confidence: 88%
“…The karyotype of A549 cell line had been analyzed by M-FISH (Park et al, 2001;Isaka et al, 2003;Cottier et al, 2004;Shen et al, 2008). Compared previous reported A549 karyotype, some differences were found.…”
Section: Comparison With Previously Published A549mentioning
confidence: 95%
“…Like GLC-82 cell line, A549 cell line also belongs to lung adenocarcinoma cell line, and has been widely used in studies of cell cycle, apoptosis and adhesion mechanisms in cancer cells (Cottier et al, 2004). The karyotype of A549 cell line was investigated by M-FISH and CGH (Park et al, 2001;Isaka et al, 2003;Cottier et al, 2004;Shen et al, 2008). But the flow-sorting of aberrant chromosomes in A549 has not been reported, nor has the reverse chromosome painting.…”
mentioning
confidence: 99%